Realities of practical andragogy in the condition of the COVID-19 pandemic: migration pedagogy in Ukraine - Deineha, Iryna; Hromozdova, Larysa; Kovach, Valeriia (ScienceRise: Pedagogical Education, 2020)
The purpose of this article is to make recommendations for the organization of adult education in quarantine conditions: exchange of experience. The article identifies that "Lifelong Learning" is one of the priorities of society in all countries, focusing on such potentials of andragogy as promoting the social adaptation of adults and addressing issues of labor migration. In the conditions of COVID-19, an effective form of work was interactive communication through e-mail, work in Viber-groups and the use of the electronic platform ZOOM for distance lectures. It has been proven, that the methods of work of a teacher and an andragogue are not identical: adult learners and full-time university students are different mental subjects of education. The theory and methodology of teaching economic disciplines in these two varieties are very different. The authors present the results of the analysis of modern scientific sources, which testify in favor of the need for further development of andragogical learning technologies. The experiment of this study and comparative analysis was not planned, it took place for objective reasons, caused by the COVID-19 pandemic. The obtained results in practical andrаgogy are useful for teachers-practitioners, andragogues, employment services - especially in cases of force majeure in adult education (COVID and others) and for quality administrative control over the learning process in extreme conditions or at a distance operating mode